The impact of student attendance on student achievement in PSAT: An Analysis of Grade 9, 10, and 11 students in an International School in Dubai - AJAJ, TASNEEM (2018)
This explanatory study is aimed at exploring the impact of attendance on PSAT achievement. The existing literature suggests that high level of attendance is correlated with high academic performance (Moonie et al., 2008; Wigley 2009; Oghuvbu, 2010) and there is no gender difference in school attainments (Lindberg et al., 2010). However, these studies were conducted predominantly in western societies such as the USA and the UK. While there are some research findings linking attendance to academic achievements, they have not established this link in relation to PSAT; hence, there is a limited research, if any, that has contributed to attendance-achievement debate from the UAE. Therefore, the current study has employed an archival research design and collected attendance and PSAT data from an international high school situated in Dubai. The school has 80% attendance policy; hence, attendance performance above 80% is considered ‘high’ attendance, while attendance lower than 79.99% is grouped under ‘low’ attendance. Based on the literature review, eight hypotheses were developed and tested using statistical analysis. Interestingly, contradictory to the predominant research findings on this topic, this study has found that there was no statistically significant impact of attendance on academic achievement. The implications of this finding for practitioners have been considered and recommendations have been provided.